'Magneto-elastic' waves in an anisotropic magnetised plasma. (14th February 2017) - Sarto, D Del; Pegoraro, F; Tenerani, A
Abstract: The linear waves that propagate in a two fluid magnetised plasma allowing for a non-gyrotropic perturbed ion pressure tensor are investigated. For perpendicular propagation and perturbed fluid velocity a low frequency (magnetosonic) and a high frequency (ion Bernstein) branch are identified and discussed. For both branches a comparison is made with the results of a truncated Vlasov treatment. For the low frequency branch we show that a consistent expansion procedure allows us to recover the correct expression of the finite Larmor radius corrections to the magnetosonic dispersion relation.